The Discharge Coffecient for Shaft Spillway According to Inlet Shape and Tail Water Conditions - Hady, Intisar A.; Mohammed, Ahmed Y. (European Journal of Applied Sciences, 2023)
The spillway is a hydraulic facility that drains excess water or in flood by transferring it from the reservoir at the inlet of the dam to the outlet. It is considered a safety element for the dam. The type of spillway depends on several factors, including the type of dam, the topographical geological nature of the ground, the highest discharge, and the frequency of the flood wave. The vertical spillway is used in cases with a finite area to create another type of spillway. In this research, three physical intake shape models were used for vertical spillway (the circular shape C, a quadrilateral shape Q, and an octagonal shape O, with two levels of tailwater: semi and wholly submerged state, and compared with free state, to study the flow behaves on the spillway. The results showed that the weir flow regime occurred in the vertical spillway intake when the ratio H/D (Head/Diameter) > 0.5, and orifice flow regime when H/D < 0.5. When the tailwater depth was wholly submerged, the water height upstream (H) was at the minimum values in the weir flow regime. The height (H) decreases when the tailwater depth is semi-submerged in the orifice flow regime. Comparison between discharge coefficient (Cd) for three intake shapes was clear; replacing intake shape (C, Q, and O) receptivity decreased Cd in the weir flow regime. On the contrary, the discharge coefficient increases at the same flow conditions in an orifice flow regime.